Concordance between timeline follow-back and single-question assessment of self-reported smoking in a clinical trial. Issue 3 (July 2016) - Bernstein, Steven L.; Rosner, June; Toll, Benjamin
Background : Smoking cessation clinical trials assess tobacco abstinence using self-report and biomarkers. Optimum methods for each are unclear; a common question assesses smoking in the prior 7 days. In contrast, timeline follow-back (TLFB) is another technique often used to assess use of alcohol in treatment trials; it is used less frequently in studies of smoking cessation. The goal of this study was to assess concordance between the 7-day smoking question and a 7-day TLFB. Methods : Secondary analysis of data from a randomized clinical trial of smoking cessation was conducted at a busy, urban hospital emergency department (ED) from October 2010 to December 2012. At 1, 3, and 12 months, subjects were contacted by phone to assess smoking status. Those reporting abstinence at 3 months were asked to return for an in-person measurement of exhaled carbon monoxide. For this analysis, smoking status at 1 month was compared for subjects in response to 2 questions asked concurrently, addressing 7-day point prevalence tobacco use and a 7-day TLFB. Results : Of 780 subjects, 666 (85.4%) were available for 1-month follow-up. Of these, 99 (14.9%) reported no smoking in response to the 7-day question, and 96 (14.4%) reported no smoking in response to the 7-day TLFB. The overall proportionate agreement between the 2 methods was 98.6%, with a kappa of 0.95 (95% confidence interval [CI]: 0.91–0.98). Conclusions : A single question that assesses smoking at 7 days provides excellent concordance with the more detailed TLFB. The single question appears adequate to assess self-reported tobacco use in clinical trials of smoking cessation.